Standard Clauses: Measuring Dilemmas in Theory - Baso, Fatihani; Uke, La Ode Muhammad Iman Abdi Anantomo; Iswandi, Iswandi; Djaoe, Andi Novita Mudriani; Ramadhani, Alya (RechtIdee, 2025)
The study aims to measure this dilemma through the theories of natural law, utilitarianism, and positivism. It employs a qualitative approach using library research and normative juridical analysis. Despite their role in enhancing transactional efficiency, standard clauses often obscure critical rights and responsibilities, particularly for consumers who lack the bargaining power or legal literacy to fully comprehend or negotiate contract terms. This condition is increasingly urgent in the context of digital transactions on e-commerce platforms, etc where standard clauses are not only more prevalent but also more opaque. Existing scholarship has yet to explore how consumer legal literacy—or the lack thereof—affects the understanding, acceptance, and contestation of standard clauses in the digital marketplace. This study fills that gap by integrating legal theory with a critical analysis of consumer awareness, offering a novel perspective on the intersection between legal formalism and substantive justice in contemporary consumer contracting. The results indicate that standard clauses are deemed unjust based on natural law theory due to their formulation often violating universal moral principles, which demand mutual agreement and fairness for all parties. According to utilitarian theory, standard clauses are beneficial if they serve all parties; however, since they mainly benefit business actors, the usefulness is limited and creates imbalance. Meanwhile, positivist theory considers standard clauses legally valid as long as they adhere to the pacta sunt servanda principle—once written and agreed upon, the contract is binding law for the parties. Although standard clauses promote business efficiency, the imbalance in bargaining power may disadvantage consumers, who must therefore critically assess their ability to accept or reject the contract.